Šiauliai Labour Camp No. 294 of Prisoners of War of Germany and its Allies (1945–1948) - Tininis, Vytautas (Genocidas ir rezistencija, 2014)
At the end of the Soviet-German war, in spring 1945, labour camps for prisoners of war of Germany and its allies were set up in Lithuania. One of them – was Šiauliai Labour Camp No. 294, which consisted of six divisions: Akmenė, Bačiūnai, Panevėžys, Pavenčiai, Radviliškis, and Šiauliai. In June 1945, 8,256 prisoners of war were imprisoned in Šiauliai Labour Camp and its divisions; on 1 January 1946, there were 5,714 prisoners remaining and on 1 June – 5,048 (4,363 worked outside the boundaries of the camp); and on 1 March 1947 – 2,583 prisoners. They were rebuilding the city of Šiauliai destroyed during the war: they rebuilt the drama theatre, 3 gymnasiums, a hospital, a railway station and other buildings. Prisoners also produced consumer goods and a variety of products at the camp workshop and did auxiliary works on the farm, so the camp was partially self-sufficient in terms of food. Prisoners, who worked in rural areas, received food from local residents. On average, there were around 3,000–4,000 prisoners in the camp each year. In terms of international humanitarian law, the repressive structures of the Soviet Union and the Lithuanian SSR basically observed the provisions of the 1929 Geneva Convention on the Treatment of Prisoners of War, but in 1945–1946 due to extremely complicated natural and economic conditions, as well as the unpredictability of the camp administration prisoners had painful experiences. Many of them were ill; in winter 1945–1946 the camp suffered a typhus epidemic. Between 1945 and 1948 about 500 prisoners died, most of the prisoners were underfed and malnourished. The camp administration and managers of various economic entities abused the available cheap labour of prisoners, corruption thrived, there was large-scale embezzlement and there were minor thefts by the camp staff. The number of prisoners fluctuated each year: some of them were taken to the Soviet Union, others were repatriated; some prisoners escaped. According to some data, between 1945 and March 1947, 188 people escaped, but according to other data between 1946 and 1947, 99 prisoners escaped (50 were recaptured) and 2,321 were repatriated. When general repatriation started in the Soviet Union, Šiauliai Labour Camp was closed in autumn 1948. The remaining inmates were transferred to Vilnius Labour Camp No. 195 and subsequently in March 1949 repatriated back to their home countries.